Association between intraoperative lactate levels and acute kidney injury after on-pump cardiac surgery: a retrospective cohort study across two centers - Dong Xu Chen; Yu Yang Zhang; Xing Long Xiong; Leng Zhou; Jing Shi (BMC Surgery)
Abstract Background Hyperlactatemia and acute kidney injury (AKI) represent significant perioperative complications in cardiac surgery. This study investigated their relationship by analyzing multiple lactate parameters during on-pump cardiac procedures. Methods In this dual-center retrospective analysis of 5255 cardiac surgery patients, we evaluated the relationship between AKI and four distinct lactate parameters: baseline, mean, peak, and time-weighted average (TWA) concentrations. The association between lactate levels and outcomes was evaluated using restricted cubic spline functions with five knots in our retrospective statistical modeling approach. Concurrently, optimal lactate thresholds were determined through the application of a classification and regression tree algorithm. Results Among the 5255 patients analyzed, 931 (17.72%) developed acute kidney injury. Statistical analysis revealed distinct patterns of association between lactate parameters and AKI risk. We identified an L-shaped relationship for mean, peak, and TWA lactate levels, contrasting with a linear association for baseline values. The study established critical thresholds for AKI risk prediction: mean lactate (2.96 mmol/L), peak lactate (4.50 mmol/L), and TWA lactate (2.33 mmol/L). Risk stratification demonstrated that patients in higher lactate quintiles faced substantially increased AKI risk, with odds ratios ranging from 1.34 to 4.37 across different lactate parameters. Conclusion These findings established specific lactate thresholds as valuable predictive markers for AKI risk in cardiac surgery, offering clinically applicable parameters for perioperative risk assessment and management. This data supported the implementation of targeted lactate monitoring strategies during cardiac procedures. Trial registration The study was registered at www.chictr.org.cn (Registration number: ChiCTR2200057320, Data of Registration: 2022-03-08).